REVIEW KERATINASE - R. L. M. Satrio Ari Wibowo; Zaenal Bachruddin; Nanung Agus Fitrianto; Tomoyuki Nakagawa; Takashi Hayakawa; Ambar Pertiwiningrum (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2017)
Proteolytic enzyme, which is able to hydrolyze keratin efficiently, is called keratinase, produced by microorganisms including fungi, bacteria and actinomycetes, and considered useful for various biotechnological approaches to waste management. Keratin is a fibrous, structural and insoluble protein, and it has high stability. Keratin is one of the main components for cell cytoskeleton, including hair and wool. Hair is difficult to degrade because it contains a lot of keratin with dense polypeptide structure, which is tightly bound by several hydrogen bonds, hydrophobic interactions, and cross-linkage of protein chain with cystine bridge. This condition makes hair have mechanical stability and resistant against degradation of proteolytic enzymes, such as pepsin, trypsin, and papain. Keratin has great strength, but it is not accumulated in nature because it can be hydrolyzed by several keratinolytic microbes. Keratinase enzyme is a part of alkaline protease group, which is active in alkaline condition. Several keratinolytic bacteria produce keratinase enzyme which remains active at pH 8 to 13. The activity of keratinase enzyme also greatly varies by temperature. Keratinase enzyme has stable activity at 20 to 70oC. Enzyme is protein which has catalytic activity and has certain molecular weight. Keratinase enzyme mostly has molecular weight which is less than 85 kDa. Enzymatic hair removal process can be used as an alternative to avoide problems caused by using sodium sulfide in tannery. The benefit of enzymatic hair removal process is perfect hair removal, so that the skin is clean and smooth; removed hair is intact; and sodium sulfide usage is minimized. Keratinase enzyme specifically degrades keratin without damaging other structural proteins, such as collagen, so it has high potential for leather industry.